1997
DOI: 10.1016/s1382-6689(97)10042-4
|View full text |Cite
|
Sign up to set email alerts
|

Food allergens

Abstract: A food allergen may be defined as a substance that reacts with IgE antibodies, induces allergic sensitisation or induces allergic reactions. Some allergens only induce allergic sensitisation but do not provoke symptoms, while others bind IgE but do not induce mast cell degranulation. There is no common structure that can predict whether a given antigen may be a strong food allergen. A complete food allergen, e.g. fish parvalbumin, is capable of stimulating the immune system to produce IgE antibodies, and degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Moreover, at least for food allergy induction, resistance of food proteins to gastric digestive enzymes seems to be decisive for allergenicity and has for a long time been regarded as predictive for their sensitizing capacity [41]. Digestion experiments with simu lated gastric uid were even considered to distinguish between potentially allergenic and non-allergenic food compounds and digestion labile food proteins were termed non-sensitizing elicitors [87,88]. However, during the past decades it has become evident that major food allergens inducing allergic sensitization via the oral route are readily degraded by gastric enzymes under physiological conditions [89].…”
Section: Discussion: Gastric Acid Reduction and Allergy Developmentmentioning
confidence: 99%
“…Moreover, at least for food allergy induction, resistance of food proteins to gastric digestive enzymes seems to be decisive for allergenicity and has for a long time been regarded as predictive for their sensitizing capacity [41]. Digestion experiments with simu lated gastric uid were even considered to distinguish between potentially allergenic and non-allergenic food compounds and digestion labile food proteins were termed non-sensitizing elicitors [87,88]. However, during the past decades it has become evident that major food allergens inducing allergic sensitization via the oral route are readily degraded by gastric enzymes under physiological conditions [89].…”
Section: Discussion: Gastric Acid Reduction and Allergy Developmentmentioning
confidence: 99%
“…AK is an abundant protein in the L. vannamei crude protein extract and it can also be considered a major shrimp allergen (fig. 1, EC lane) [26,27,28]. The fact that AK protein kept its allergenic activity in denaturing condition (SDS-PAGE) showed that interaction with IgE is probably shared by a lineal rather than a conformational epitope.…”
Section: Discussionmentioning
confidence: 99%
“…No common structure can predict whether an antigen may be an allergen but generally allergens resist enzymatic hydrolysis in the gastrointestinal tract (see review by Aalberse, 1997).…”
Section: Allergens General Characteristicsmentioning
confidence: 99%